2012
DOI: 10.5506/aphyspolbsupp.5.947
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Bulk and shear viscosity coefficients for systems composed of quasiparticles with medium-modified dispersion relations are determined within an effective kinetic theory approach of Boltzmann-Vlasov type. Local conservation of energy and momentum, which is self-consistently embedded in the kinetic theory, implies in thermal equilibrium thermodynamic consistency in quasiparticle approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The results in this paper have been used extensively in our analysis of parton energy loss in unstable QGP, a preliminary account of which is published as Refs. [19][20][21]. We hope that the analysis we have presented in this paper will facilitate computations of other characteristics of anisotropic QGP.…”
Section: Summary and Final Remarksmentioning
confidence: 97%
See 1 more Smart Citation
“…The results in this paper have been used extensively in our analysis of parton energy loss in unstable QGP, a preliminary account of which is published as Refs. [19][20][21]. We hope that the analysis we have presented in this paper will facilitate computations of other characteristics of anisotropic QGP.…”
Section: Summary and Final Remarksmentioning
confidence: 97%
“…A particularly interesting quantity is the energy loss of a highly energetic parton traversing an unstable QGP, which depends crucially on the spectrum of collective excitations (a preliminary account of our energy-loss study can be found in Refs. [19][20][21]). Complete information about the collective modes of an anisotropic system is therefore important and useful.…”
Section: Introductionmentioning
confidence: 99%
“…To compute the energy loss using the formula (28) we have to invert the matrix Σ defined by Eq. (21) or (23), which is the inverse gluon propagator in the temporal axial gauge. In isotropic plasmas the matrix depends on only one vector k. It can be decomposed into transverse and longitudinal components and is therefore easily inverted giving Eq.…”
Section: A Propagatormentioning
confidence: 99%
“…A preliminary account of our findings was published in the series of conference proceedings [21][22][23][24]. In these reports, we used a specific choice of initial conditions and we were not aware that our results crucially depend on this choice, to the extent that the test parton can not only loose energy in an unstable plasma, but could also gain the energy, depending on how the initial conditions are chosen.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25]. In this work we consider a stable plasma, for which all modes are damped and there are no instabilities.…”
Section: Collisional Energy Lossmentioning
confidence: 99%